Inflection Point as a Manifestation of Tricritical Point on the Dynamic Phase Boundary in Ising Meanfield Dynamics (Communications in Computational Physics, 2018)
We studied the dynamical phase transition in kinetic Ising ferromagnetsdriven by oscillating magnetic field in meanfield approximation. The meanfield differential equation was solved by sixth order Runge-Kutta-Felberg method. We calculated the transition temperature as a function of amplitude and frequency of oscillating field. This was plotted against field amplitude taking frequency as a parameter.As frequency increases the phase boundary is observed to become inflated. The phaseboundary shows an inflection point which separates the nature of the transition. Onthe dynamic phase boundary a tricritical point (TCP) was found, which separates thenature (continuous/discontinuous) of the dynamic transition across the phase boundary. The inflection point is identified as the TCP and hence a simpler method of determining the position of TCP was found. TCP was observed to shift towards high fieldfor higher frequency. As frequency decreases the dynamic phase boundary is observeto shrink. In the zero frequency limit this boundary shows a tendency to merge to thetemperature variation of the coercive field.